Sep acceleration in CME driven shocks using a hybrid code - Gargaté, L. (2014)
We perform hybrid simulations of a super-Alfvénic quasi-parallel shock, driven by a coronal mass ejection (CME), propagating in the outer coronal/solar wind at distances of between 3 to 6 solar radii. The hybrid treatment of the problem enables the study of the shock propagation on the ion timescale, preserving ion kinetics and allowing for a self-consistent treatment of the shock propagation and particle acceleration. The CME plasma drags the embedded magnetic field lines stretching from the sun, and propagates out into interplanetary space at a greater velocity than the in situ solar wind, driving the shock, and producing very energetic particles. Our results show that electromagnetic Alfvén waves are generated at the shock front. The waves propagate upstream of the shock and are produced by the counter-streaming ions of the solar wind plasma being reflected at the shock. A significant fraction of the particles are accelerated in two distinct phases: first, particles drift from the shock and are accelerated in the upstream region, and second, particles arriving at the shock get trapped and are accelerated at the shock front. A fraction of the particles diffused back to the shock, which is consistent with the Fermi acceleration mechanism.